2015
DOI: 10.1123/pes.2014-0175
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Validation of Aerobic Capacity Prediction Models in Adolescents

Abstract: Cardiorespiratory endurance is a component of health-related fitness. FITNESSGRAM recommends the Progressive Aerobic Cardiovascular Endurance Run (PACER) or One mile Run/Walk (1MRW) to assess cardiorespiratory endurance by estimating VO2 Peak. No research has cross-validated prediction models from both PACER and 1MRW, including the New PACER Model and PACER-Mile Equivalent (PACER-MEQ) using current standards. The purpose of this study was to cross-validate prediction models from PACER and 1MRW against measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 0 publications
1
32
0
2
Order By: Relevance
“…Some grey literature sources were not included because they were published later in a journal paper, e.g. [ 144 – 146 ]. From the Cureton’s et al [ 51 ] study the correlation coefficient with the only performance score was not included because the data came from the sum of some samples that had been reported in other journal papers [ 49 , 50 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some grey literature sources were not included because they were published later in a journal paper, e.g. [ 144 – 146 ]. From the Cureton’s et al [ 51 ] study the correlation coefficient with the only performance score was not included because the data came from the sum of some samples that had been reported in other journal papers [ 49 , 50 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…If the student twice failed to reach the other floor marker within the allotted time frame, the test was terminated. Because estimated VO 2 Peak relates stronger to cardio-metabolic health than field test performance scores, PACER laps were converted to estimated VO 2 Peak using a validated prediction equation currently used by the FITNESSGRAM battery (Burns et al, 2015). The derived VO 2 Peak score was used as a covariate in the proceeding analysis.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, a significant association between the time to complete 1600 m and CRF was worth extra attention. The studies (Burns et al, 2015;Pober, Freedson, Kline, McInnis, & Rippe, 2002) indicated that the time to complete 1600 m was significantly negatively related with CRF. The studies indicated that higher-CRF individuals had higher neurocognitive function, shorter reaction time and more accurate response (Chaddock et al, 2010;Dupuy et al, 2015), which might benefit in elevating academic performance.…”
Section: Discussionmentioning
confidence: 99%